MENCANDRA POTRET NERAKA DALAM PERSPEKTIF AL-QUR’AN - Syarifuddin Syarifuddin; Setiawan Setiawan (STIT AL-AMIN KREO TANGERANG, 2022)
The atmosphere of hell and the state of its inhabitants are depicted in the Qur'an very graphically. A very terrible atmosphere of hell, that is; fires that never go out, fuel from humans and rocks. The image of hellfire that continues to burn for thousands of years is black which results in everything in it becoming black, including the inhabitants of the jinn and humans. As for the condition of the inhabitants, neither alive nor dead, so they only want one of two things, death or relief, but neither is given. In addition, they are always desperate because there is no hope of going out, every time they want to go out, they will be returned to hell. As for the food and drink that did not give glut and crossed thirst, but instead added to the torment for him and they were also given clothes made of very hot tar that tormented them to their bones.